2020
DOI: 10.1063/5.0002372
|View full text |Cite
|
Sign up to set email alerts
|

Defect limitations in Cu2ZnSn(S, Se)4 solar cells utilizing an In2S3 buffer layer

Abstract: Alternative n-type buffer layer such as In 2 S 3 have been proposed as Cd-free alternative in kesterite Cu 2 ZnSn(S,Se) 4 (CZTSSe) solar cells. In this study, optical and electronic characterisation techniques together with device analysis and simulation were used to assess nanoparticle-based CZTSSe absorbers and solar cells with CdS and In 2 S 3 buffers. Photoluminescence spectroscopy indicated CZTSSe absorbers with In 2 S 3 buffer had a lower density of detrimental non-radiative defects and a higher concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 80 publications
(100 reference statements)
1
20
0
Order By: Relevance
“…These IS results is in good agreement with dark J–V and EQE results. Therefore, it can be concluded that this photo‐doping effect suggests that the In 2 S 3 layer, as an additional buffer layer, forms a high‐energy barrier hindering the interfacial charge transfer if it becomes too thick (e. g., over 20 nm) [17,45] . A brief band diagrams of CZTSSe/In 2 S 3 /CdS is presented for showing the photo‐doping effect (Figure S10).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These IS results is in good agreement with dark J–V and EQE results. Therefore, it can be concluded that this photo‐doping effect suggests that the In 2 S 3 layer, as an additional buffer layer, forms a high‐energy barrier hindering the interfacial charge transfer if it becomes too thick (e. g., over 20 nm) [17,45] . A brief band diagrams of CZTSSe/In 2 S 3 /CdS is presented for showing the photo‐doping effect (Figure S10).…”
Section: Resultsmentioning
confidence: 99%
“…The highest certified and reported efficiencies of CZTSSe thin‐film solar cells are 13.0 % (NREL efficiency chart) and 12.6 %, [3,12] respectively; however, this value is much lower than the theoretical efficiency of CZTS‐based single junction cells [i. e., 32.4 % with short‐circuit current density ( J SC )=29.6 mA ⋅ cm −2 , open‐circuit voltage ( V OC )=1.21 V, and fill factor (FF)=89.9 %] calculated using the Shockley–Queisser efficiency limit [13] . In terms of efficiency improvement, CZTSSe thin‐film solar cells mainly suffer from large V OC deficits ( E g / q – V OC ; E g is the band gap energy and q is the electron charge) originating from the severe non‐radiative recombination in the bulk and at the charge separation interfaces [14–18] . In particular, defects such as antisite defects (e. g., Cu Zn , Cu Sn , Sn Cu , and Sn Zn ), vacancies (e. g., V Zn , V Sn , and V Cu ), and defect clusters (e. g., 2Cu Zn +Sn Zn ) along with the secondary phase can easily be created in the CZTSSe bulk and at the interface because of the narrow phase stability region of the pure CZTSSe in the thermodynamic phase diagram [18–20] .…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations